(untitled) (European journal of volunteering and community-based projects, 2021)
The paradigm generated on world systems and models by COVID-19 has led to the search for new solutions. The European Commission has generated and strengthened the previously defined sustainability and Green Deal policies. The NextGenerationEU fund could incentivize the application and adoption of the actions. The analysis intends to analyze how COVID-19 changed policies undertaken before the pandemic and how these were redefined. A content analysis (CA) technique, through LEXIMANCER software, is adopted to answer the research questions considering articles collected by the Business Source Ultimate platform from February 2020 to June 2021 in Europe. The analysis identified 35 key concepts that describe the path and approach that influenced and guided the new Green Deal policies. The analysis identifies the main areas on which an impact is expected and the confirmation or variation of the approach.